Improving clinical leadership and management in the NHS - Nicol ED (Journal of Healthcare Leadership, 2012)
Edward D Nicol1,21Department of Cardiology, Royal Brompton Hospital and Harefield NHS Trust, London, United Kingdom; 2Clinical Leadership Academy, School of Medicine, Keele University, Staffordshire, United KingdomAbstract: The National Health Service (NHS) is one of the UKs most cherished but political public institutions, providing healthcare, free at the point of delivery. The English NHS must make £20bn efficiency savings in the next 3 years whilst in the midst of fundamental structural change outlined in the government's Health and Social Care Bill. This paper will explore the history of leadership and management in the NHS; the evolution of clinical leadership; national strategies to improve NHS clinical and managerial leadership and Lord Darzi's pivotal NHS review. It defines the kind of leadership and management required for today's NHS, looking to overcome some of the main challenges such as improving healthcare quality whilst making efficiency savings and engaging grass roots workers to deliver sustainable, long term improvements. Finally this manuscript makes suggestions as to where future investment is required to improve clinical leadership and management in the NHS.Keywords: clinical leadership, healthcare management, national health service